Genetic distinctiveness of safflower cultivars of India and Mexico as revealed by SSR markers. Issue 6 (29th June 2016) - Kadirvel, P.; Ravi, D.; Mukta, N.; Montoya-Coronado, M.C.L.; Ghuge, S.B.; Singh, J.; Singh, V.; Shinde, S.K.; Deshmukh, S.N.; Yadav, P.; Varaprasad, K.S.
Abstract: Safflower is a traditional oilseed crop in the world. Its seed oil is a healthy edible oil containing high amount of unsaturated fatty acids. Genetically diverse exotic cultivars are valuable germplasm for introducing new diversity in safflower improvement programmes. In this study, we characterized safflower cultivars of India (30) and Mexico (23) comprising varieties, hybrids and advanced lines developed over 50 years for genetic distinctiveness using 38 simple sequence repeat (SSR) loci. Genetic diversity estimates across cultivar groups (total, India and Mexico) were as follows: mean number of alleles (3.2, 3.1, 2.6), expected heterozygosity (0.42, 0.37, 0.37) and polymorphism information content (0.36, 0.33, 0.32) respectively, which suggested narrow SSR allelic diversity within and between cultivar groups. However, distance-based cluster analysis (neighbour-joining tree) and model-based STRUCTURE analysis revealed that safflower cultivars of India and Mexico, with the exception of a few, form two genetically distinct groups. High level of genetic variation explained between the populations (40%) and Fst estimate (0.4) suggested that the cultivar groups were highly differentiated with limited gene flow supporting a strong genetic structuring. High oil (~38%) and high oleic (73–79%) contents of a subset of Mexican safflower varieties and advanced lines were confirmed in field trials in India. These exotic sources from Mexico are valuable for safflower breeding programmes in India to develop new cultivars with high oil yielding potential and high oleic acid content, which is the current market demand.